Demagnetization Faults Robust Detection Method Based on an Adaptive Sliding Mode Observer for PMSM - Zhang, Changfan; Zhang, Miaoying; He, Jing; Shao, Rui; Luo, Lixiang (Journal of advanced computational intelligence and intelligent informatics, 2016)
To detect demagnetization faults in real time based on an adaptive sliding mode observer, we used a permanent-magnet synchronous motor (PMSM). Demagnetization faults are first modeled for the PMSM using coordinates oriented to the magnetic field. To solve demagnetization faults problems as multiple parameters change, we used adaptive and sliding mode variable structure control and designed an adaptive sliding mode observer. The adaptive estimation algorithm of the permanent magnet flux is given and the observer’s stability is proven by Lyapunov stability theory. Simulation and experimental results demonstrate the feasibility and effectiveness of our proposal.